178k views
0 votes
How do you solve 0.3+1.4(x+1)=4.4x+8.3-3x

User Nchpmn
by
5.9k points

1 Answer

2 votes

Answer:

x=6.7

Explanation:

To solve this problem is necessary to perform basic operations in order to reduce the amount of work.

This means that we need to sum coefficients of 'x' in boths side of equations, and do the same thing to free terms.

Therefore, The expression 0.3+1.4(x+1)=4.4x+8.3-3x, becomes

0.3+1.4(x+1)=4.4x+8.3-3x

1.4x+1.7=1.1x+8.3

Next

Lets isolate x variable in one side of equality sign

1.4x+1.1x=8.3+1.7

1.5x=10

x=10/1.5

User Taha Paksu
by
5.8k points